A novel MIR100HG transcript enhances tumorigenesis by inducing BCLAF1-mediated alternative splicing in colorectal cancer - Mingrui Dai; Yuhua Shi; Hailin Zhao; Yue Hu; Xianling Cong; Bin Yu; Haihong Zhang; Xianghui Yu; Hui Wu (Cell Communication and Signaling)
Abstract Background Long non-coding RNAs (lncRNAs) play crucial roles in cancer pathogenesis, including colorectal cancer (CRC). Distinct lncRNA transcripts from the same gene show diverse regulatory roles in cancer. The MIR100HG, a lncRNA gene characterized by multiple transcript variants, has been implicated in promoting CRC oncogenesis. However, the specific functions of individual MIR100HG transcripts in tumorigenesis remain unclear. Methods We explored the MIR100HG transcripts upregulated by TGFβ1 treated in CRC cells using RNA-Seq and characterized a novel transcript in CRC cells and tumor tissues via qRT-PCR. Chromatin immunoprecipitation and luciferase assays revealed this transcript’s upstream regulation. Functional experiments were performed in vitro and in mouse models. The molecular mechanism was elucidated through RNA-seq, RNA pull-down, mass spectrometry, RNA immunoprecipitation and co-immunoprecipitation. Finally, we evaluated the transcript’s therapeutic potential by treating mouse model tumors with antisense oligonucleotide. Results We identified a novel transcript, MIR100HG-L, which retains more portion of exon 1 compared to the previously reported shorter transcript. MIR100HG-L was transcriptionally upregulated by TGFβ/SMAD signaling and exhibited elevated expression in CRC tissues. Functionally, this transcript was demonstrated to promote CRC cell proliferation, suppress apoptosis and enhance drug resistance. Mechanistically, MIR100HG-L specifically interacted with BCLAF1, serving as a protein scaffold to connect BCLAF1 with splicing factors. This interaction significantly induced BCLAF1-mediated splicing events of oncogenes related to apoptosis and DNA damage response, enhancing their expression and contributing to CRC development. MIR100HG-L-targeted antisense therapy reduced tumor growth and increased cetuximab sensitivity. Conclusions Our study reveals a novel MIR100HG transcript induced by TGFβ/SMAD signaling and explores its distinct oncogenic mechanism through a structure-specific interaction with the BCLAF1. These findings suggest distinct MIR100HG transcripts may exert diverse functions and lead to the identification of novel molecular markers and therapeutic targets for CRC.